2021
DOI: 10.1136/neurintsurg-2021-018078
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral venous outflow profiles are associated with the first pass effect in endovascular thrombectomy

Abstract: BackgroundRecent studies found that favorable venous outflow (VO) profiles are associated with higher reperfusion rates after mechanical thrombectomy (MT) in patients with acute ischemic stroke due to large vessel occlusion (AIS-LVO). Fewer retrieval attempts and first-pass revascularization during MT lead to better functional outcomes.ObjectiveTo examine the hypothesis that favorable VO profiles assessed on baseline CT angiography (CTA) images correlate with successful vessel reperfusion after the first retri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…The score is obtained by grading the opacification of three major cortical veins, namely the superficial middle cerebral vein, vein of Labbé, and sphenoparietal sinus, on a scale from 0 to 2 points (0, not visible; 1, moderate opacification; 2, full opacification). A favorable VO was defined as COVES ≥3 based on previous studies [ 17 , 20 ]. VO grading was independently performed by two neuroradiologists (T.D.F.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The score is obtained by grading the opacification of three major cortical veins, namely the superficial middle cerebral vein, vein of Labbé, and sphenoparietal sinus, on a scale from 0 to 2 points (0, not visible; 1, moderate opacification; 2, full opacification). A favorable VO was defined as COVES ≥3 based on previous studies [ 17 , 20 ]. VO grading was independently performed by two neuroradiologists (T.D.F.…”
Section: Methodsmentioning
confidence: 99%
“…A favorable VO was defined as COVES ≥3 based on previous studies. 17,20 VO grading was independently performed by two neuroradiologists (T.D.F. and J.J.H., with 10 and 15 years of working experience) with substantial inter-reader agreement.…”
Section: Image Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…1,19 Multiple studies reported of a strong association of favorable VO profiles with good procedural and long-term clinical outcomes, which warrants further investigation of venous microvascular changes in patients treated with tPA before EVT. 1,4,8,17–20,38…”
Section: Discussionmentioning
confidence: 99%